Avalia????o neurofisiol??gica e funcional em pacientes com doen??a pulmonar obstrutiva cr??nica e com asma de dif??cil controle - Canuto, Fabiana Freitas (2010)
The influence on lung diseases and physical inactivity can lead to compromising the neurophysiological activity of normal skeletal muscles. Objective: To examine the neuropsychological effectiveness of the sit-ups test, comparing it to the six-minute walk test (6MWT) in patients with chronic obstructive pulmonary disease (COPD) and evaluate the neurophysiological aspects and functional capacity in individuals with difficult to control asthma. Method: Two studies were performed: in the first one, two methods were used, the sit-ups test and 6MWT; with arterial blood collection for measurement of blood lactate concentration and electromyography in this way. In the second study, patients were divided into two groups plus a control group who underwent completion of sit-ups test and the 6MWT to evaluate the functional capacity of reflex latency of the monosynaptic patellar reflex and Achilles which was assessed with surface electromyography; the assessment of peripheral muscle strength of the quadriceps using the load cell, and finally the static equilibrium was analyzed by the oscillating pressure center by the force platform. Results: The blood lactate concentration at rest and end of functional activities as well as the angular coefficients (AC) obtained from the median frequency showed a statistically significant difference (p = 0.0005) between baseline and end of the sit-ups test individuals with COPD, in patients with ADC, which make use of oral corticosteroids (ADCC) and making use of Omalizumab (ADCO) compared with the control group (CG) reflex latency time and static balance are within normal limits, while the functional capacity is reduced in relation to peripheral muscle strength only on group ADCC presented below. Conclusion: We found a correlation between the two neurophysiological functional tests, and we suggest that the sit-ups test can determine the functional status as easily as the 6MWT in terms of neurophysiological effectiveness. Patients with ADC show a reduction in functional capacity seen in 6MWT and sit-ups test (p <0.05), and patients who use oral corticosteroids showed a reduction of quadriceps strength compared to control (p < 0.05).